2016
DOI: 10.1371/journal.pone.0148466
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Modal and Intra-Modal Characteristics of Visual Function and Speech Perception Performance in Postlingually Deafened, Cochlear Implant Users

Abstract: Evidence of visual-auditory cross-modal plasticity in deaf individuals has been widely reported. Superior visual abilities of deaf individuals have been shown to result in enhanced reactivity to visual events and/or enhanced peripheral spatial attention. The goal of this study was to investigate the association between visual-auditory cross-modal plasticity and speech perception in post-lingually deafened, adult cochlear implant (CI) users. Post-lingually deafened adults with CIs (N = 14) and a group of normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 59 publications
4
31
0
Order By: Relevance
“…However, the correlational analysis presented in the current results suggest that greater degrees of cross-modal reorganization are associated with poorer speech perception in noise scores. Interestingly, consistent with the present study, there is some evidence to support the notion that the right temporal cortices are more susceptible to functional reorganization, although the reason for this effect remains to be determined (Finney et al, 2001 ; Sandmann et al, 2012 ; Campbell and Sharma, 2013 , 2014 , 2016 ; Cardin et al, 2013 ; Lin et al, 2014 ; Kim et al, 2016 ; Peelle and Wingfield, 2016 ; Sharma et al, 2016 ; Shiell et al, 2016 ).…”
Section: Discussionsupporting
confidence: 89%
“…However, the correlational analysis presented in the current results suggest that greater degrees of cross-modal reorganization are associated with poorer speech perception in noise scores. Interestingly, consistent with the present study, there is some evidence to support the notion that the right temporal cortices are more susceptible to functional reorganization, although the reason for this effect remains to be determined (Finney et al, 2001 ; Sandmann et al, 2012 ; Campbell and Sharma, 2013 , 2014 , 2016 ; Cardin et al, 2013 ; Lin et al, 2014 ; Kim et al, 2016 ; Peelle and Wingfield, 2016 ; Sharma et al, 2016 ; Shiell et al, 2016 ).…”
Section: Discussionsupporting
confidence: 89%
“…Cross-modal reorganization is typically interpreted as a deprivation-induced residual of cortical changes that impedes on speech recovery. Some studies found a maladaptive relationship between processing differences and speech perception in CI users, more specifically, CI users with a higher amount of cross-modal reorganization show a poorer performance in speech perception ( Buckley and Tobey, 2011 , Campbell and Sharma, 2014 , Doucet et al, 2006 , Kim et al, 2016 , Sandmann et al, 2012 ). One has to keep in mind that, in contrast to source estimation as in the current study, some of these correlations are based on scalp EEG analyses, which cannot easily disentangle contributions from different cortical generators (cf.…”
Section: Discussionmentioning
confidence: 99%
“…To date studies of cross-modal interactions in deaf individuals with CIs have typically reported broad correlations between VEPs and behavioral measures of speech understanding (e.g., Doucet et al, 2006 ; Buckley and Tobey, 2011 ; Sandmann et al, 2012 ; Kim et al, 2016 ). In the present study, we have the ability to examine more directly the relationship between auditory and visual activity.…”
Section: Relationship Between Auditory and Visual Datamentioning
confidence: 99%
“…Recent work has reported evidence of CMP in pre- and post-lingually deaf adults with CIs which has been suggested to be maladaptive. In studies that have reported maladaptive CMP, the research often makes use of a neural marker of visual processing (e.g., P1 or N1 evoked potentials), and relates this signal to a behavioral processing deficit such as identification of speech in noise ( Doucet et al, 2006 ; Buckley and Tobey, 2011 ; Sandmann et al, 2012 ; Campbell and Sharma, 2016 ; Kim et al, 2016 ). The inference is then made that the altered visual response is causally related to the auditory speech processing and, by association, that auditory cortical regions are vulnerable to reorganization ( Sharma et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%